2014
DOI: 10.1002/14651858.cd006546.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Kinship care for the safety, permanency, and well-being of children removed from the home for maltreatment

Abstract: This review supports the practice of treating kinship care as a viable out-of-home placement option for children removed from the home for maltreatment. However, this conclusion is tempered by the pronounced methodological and design weaknesses of the included studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 248 publications
4
34
0
2
Order By: Relevance
“…The original review was coregistered with the Cochrane Collaboration and Campbell Collaboration and was published in 2009 (Winokur, Holtan, & Valentine, 2009). In keeping with Cochrane Collaboration policy, we updated the review to include studies published between March 2007 and March 2011 (Winokur, Holtan, & Batchelder, 2014).…”
Section: Study Purposementioning
confidence: 99%
“…The original review was coregistered with the Cochrane Collaboration and Campbell Collaboration and was published in 2009 (Winokur, Holtan, & Valentine, 2009). In keeping with Cochrane Collaboration policy, we updated the review to include studies published between March 2007 and March 2011 (Winokur, Holtan, & Batchelder, 2014).…”
Section: Study Purposementioning
confidence: 99%
“…Social work policy in recent years has favoured the placement of children with kinship carers over traditional foster care given the research evidence showing that children placed with kinship carers fare better than children placed with foster parents who have no kinship ties to the child (Winokur et al . ). Based on a Cochrane meta‐analysis of 62 studies, Winokur and colleagues found that children placed with kinship carers displayed lower levels of internalizing and externalizing behaviour problems and greater competence in adaptive behaviours when compared with children in foster care.…”
Section: Introductionmentioning
confidence: 97%
“…However, in my experience, Australian social Australian Social Work 285 workers are often unaware of this resource that may support their practice. Recent Cochrane reviews of interest to social workers include "Efficacy and experiences of telephone counselling for informal carers of people with dementia" (Lins et al, 2014) and "Kinship care for the safety, permanency, and well-being of children removed from the home for maltreatment" (Winokur, Holtan, & Batchelder, 2014). Similarly, there is limited awareness of the Campbell Collaboration that was founded in 2000 on similar lines to the Cochrane Collaboration but with a focus on systematic reviews on social interventions in fields such as education, criminal justice, and social welfare (Petrosino, 2013).…”
mentioning
confidence: 99%